Analyzing the Structure of Administrative System of Hormozgan and its Adaptation to the Perspective of 1404 with the Land Use Planning Approach - Zaeri Zadeh, Mostafa (2021)
The present study aimed to analyze the structure of administrative systems in Hormozgan and its adaptation to the 1404 perspective with the land use planning (land preparation) approach. This paper is applied in purpose and is descriptive-analytical in nature. The statistical population of this research is Hormozgan as one of the Iran provinces. In order to collect information on the theoretical foundations and research literature, library resources, articles and required books were used and indicators of the administrative system structures (staff, development budget, planning system, spatial structure and free zones) were identified. The required quantitative data was extracted and classified based on census and housing results during 2006- 2017 and after quantitative calculations, they were analyzed in order to adjust with the 1404 goals. In order to analyze the information, time series and factor analysis methods and central tendencies and dispersion were used. SPSS version 24, MINTAB version 17, AMOS version 24 and excel were used for data analysis. Based on the results, considering that there was a significant difference between the value of the mean calculated for each of the factors of the administrative system structure during 2006-2017 (the current administrative system of Hormozgan) and the values related to the administrative system of perspective 1404, so it can be said that there is a difference between the current administrative system of Hormozgan and the perspective of 1404 with the land use planning approach.